Removal of Chloride from Ground Water Using Natural Adsorbent: Water Hyacinth - Akanksha V. Pisolkar (International Journal of Pollution: Prevention & Control, 2024)
Groundwater contaminants in rural areas often include chlorides and hardness. Nowadays, due to water scarcity, there is a need to utilize groundwater for construction purposes. According to IS 456:2000, the chloride content in water used for mixing and curing concrete must not exceed 2000 mg/l for plain concrete and 500 mg/l for reinforced concrete work. An excess amount of chloride in water causes the deterioration of structures. Concrete durability and strength can be compromised by hard water, characterized by elevated mineral levels. This study aims to devise an efficient treatment system capable of lowering chloride and hardness concentrations in groundwater to acceptable levels while minimizing treatment costs. The water hyacinth plant is used as a natural absorbent in this process. The adsorption capacity of water hyacinth is determined through studies, including parameters such as the initial concentration of influent, contact time of influent and absorbent layer, and flow rate of influent. This study shows that the chloride content of the water sample is reduced by 17%-20%, and the hardness is reduced by 20-25%.
Keywords: Chloride ions; Hardness; Natural Absorbent; biodegradability; water hyacinth